1999
DOI: 10.1523/jneurosci.19-21-09170.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer's Disease Amyloid Precursor Protein Modulates Copper-Induced Toxicity and Oxidative Stress in Primary Neuronal Cultures

Abstract: The amyloid precursor protein (APP) of Alzheimer's disease can reduce copper (II) to copper (I) in a cell-free system potentially leading to increased oxidative stress in neurons. We used neuronal cultures derived from APP knock-out (APP(-/-)) and wild-type (WT) mice to examine the role of APP in copper neurotoxicity. WT cortical, cerebellar, and hippocampal neurons were significantly more susceptible than their respective APP(-/-) neurons to toxicity induced by physiological concentrations of copper but not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(159 citation statements)
references
References 62 publications
7
151
1
Order By: Relevance
“…This observation brings to mind the associations previously noted between oxidative stress, metal ions, and the toxicity of A␤ or APP (26,27), and indirect measures of lipid peroxidation that have more recently showed that oxidative stress correlates with amyloid plaque formation in animal models (28), and with disease severity in humans (29). It is also noteworthy that vitamin E, a lipophilic antioxidant, is relatively deficient in the post-mortem brain tissue of patients of Alzheimer's disease (30), and its administration in pharmacological doses appears to slow the clinical progression of disease (31).…”
mentioning
confidence: 68%
“…This observation brings to mind the associations previously noted between oxidative stress, metal ions, and the toxicity of A␤ or APP (26,27), and indirect measures of lipid peroxidation that have more recently showed that oxidative stress correlates with amyloid plaque formation in animal models (28), and with disease severity in humans (29). It is also noteworthy that vitamin E, a lipophilic antioxidant, is relatively deficient in the post-mortem brain tissue of patients of Alzheimer's disease (30), and its administration in pharmacological doses appears to slow the clinical progression of disease (31).…”
mentioning
confidence: 68%
“…APP KO mice are viable and fertile but suffer from various defects and abnormalities, such as reduced body and brain weight, decreased size of forebrain commissures, increased frequency and severity of corpus callosum agenesis [28,30], reactive gliosis [28], increased sensitivity to kainate-induced seizures [36], increased copper and iron levels in the cerebral cortex and liver [37,38], upregulated cholesterol and sphingomyelin levels in the brain [39] and decreased plasma glucose levels as well as hyperinsulinemia [40]. Behavioral studies revealed that APP KO mice have decreased locomotor activity, reduced forelimb grip strength and deficits in the Morris water maze task as well as passive avoidance learning [41][42][43].…”
Section: App Aplp1 and Aplp2 Single Ko Micementioning
confidence: 99%
“…APP is an integral membrane protein with high affinity for copper (39,40). It has been suggested that APP is involved in neurodevelopment (41) and is essential for neuronal growth (42,43).…”
Section: ␤-Amyloid (A␤)mentioning
confidence: 99%